PERCEPATAN PEMIJAHAN LELE DENGAN INDUKSI LASERPUNKTUR UNTUK MEMPRODUKSI BENIH SKALA MASSAL - Dyah Hariani; Pungky Slamet Wisnu Kusuma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The seedling unit of Mulyorejo is one breeder catfish has implemented the way of a good and true fish hatchery system and quality of seeds produced and certified so that many invaded by consumers of catfish enlargement group. But the problem is that the UPR has not been able to needs of consumers seed. UPR is targeting production of 12 million of seeds during the rainy season, but in reality only able to supply seeds of catfish in the market about 5 million fries so that there is a shortage of 7 million fries. Therefore, it is necessary that the appropriate technology breakthroughs Laserpuncture technology to accelerate the provision of gonads mature broodstock catfish and catfish seed supplies in bulk and continuously to support the success, sustainability and development of catfish farming through socialization. The method is applied to training programs for the dissemination of technology laserpuncture as an effort to accelerate the broodstock catfish mature gonads and seed production a mass scale in the group breeder catfish